2011
DOI: 10.1109/tvt.2011.2165741
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Prefix Construction for OFDM Systems Over Quasi-Static Channels

Abstract: All practical OFDM systems require a prefix to eliminate inter-symbol interference at the receiver. Cyclic prefix (CP) and zero-padding are well-known prefix construction methods, the former being the most employed technique in practice due to its lower complexity. In this paper we construct an OFDM system with a generalized CP. It is shown that the proposed generalized prefix effectively makes the channel experienced by the packet different from the actual channel. Using an optimization procedure, lower bit e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 22 publications
0
21
0
3
Order By: Relevance
“…Genelleştirilmişönek'in SISO durumunda daha iyi bir performans gösterdigi [10]'da gösterilmiştir.İyileştirme derin sönümlü veya izgesel sıfıra sahip kanallar için daha da büyüktür.…”
Section: Ofdm Si̇nyal Modeli̇unclassified
See 2 more Smart Citations
“…Genelleştirilmişönek'in SISO durumunda daha iyi bir performans gösterdigi [10]'da gösterilmiştir.İyileştirme derin sönümlü veya izgesel sıfıra sahip kanallar için daha da büyüktür.…”
Section: Ofdm Si̇nyal Modeli̇unclassified
“…Bu makalenin amacı, [10]'daki yaklaşımın MIMO durumunda da uygulanabilir oldugunu göstermektir. Genelleme kaybı olmadan iki verici iki alıcı antenli bir sistem gözönünde bulundurulmuştur.…”
Section: Mimo-ofdm Durumuunclassified
See 1 more Smart Citation
“…Recently, another prefix construction technique called generalised prefix (GP) was proposed for OFDM systems [17] that also diagonalises the channel matrix, that is, the CP is not the only prefix with this property. It was also shown that this GP-OFDM system has the lowest BER among the other prefix construction techniques, considering all other parameters identical.…”
Section: Introductionmentioning
confidence: 99%
“…The paper is organised as follows: In Section 2, we discuss the OFDM system model to introduce the notations. The signal model in [17] is simplified and written as a vector-matrix form for single-input single-output (SISO) systems, which, in turn, is easier to apply to the MIMO case. In Section 3, we develop STBC-GP-OFDM.…”
Section: Introductionmentioning
confidence: 99%